Growth and characterization of amorphous Si based multilayer structures - Kamyab, Lobna (2013)
Silicon is a widely available material with very good electrical, thermal and mechanical properties suitable for the manufacture of electronic devices and has contributed to the big success of microelectronics. The trend in Si microelectronics towards faster and smaller devices has resulted in many issues such as heat dissipation, crosstalk and RC delay in metal interconnects. To address these issues while achieving faster inter-component communication and keeping the costs low, Si microphotonics which focuses on the development of Si based phtonics devices has been actively pursued. Todate almost all Si based optoelectronic components, such as waveguides, detectors and modulators have been realized except for an efficient light source. Many attempts have been made to obtain visible light emission from Si utilizing amorphous Si (a-Si) and/or Si nanostructures. These include porous Si, Si nanocrystals embedded in a dielectric matrix. Another approach to based low dimensional Si based materials to achieve light emission, is to utilize multilayer structures. These structures have the advantages of reproducibility and thickness controllability, which makes them leading competitors in this field. In this work we have fabricated a-SiNx:H/SiO2 multilayer quantum well structures consisting of 20 alternating layers of a-SiNx:H and SiO2 using the plasma enhanced chemical vapor deposition (PECVD) technique. a-SiNx:H has been chosen as it is an efficient light emitting material and its bandgap can be tuned in a wide energy range. This property will give rise to greater flexibility in controlling and optimizing the emission characteristics. With the prospect of optimizing the N content in our a-SiNx:H material for its light emission we have started with studying single layer a-SiNx:H material. They have been grown by varying the Si source gas (SiH4) and N source gas (NH3) flow ratio in the range of 1.05 to 3.16. Their optical properties, including the bandgap, Urbach energy and complex refractive indices were obtained by a detailed study of their spectroscopic ellipsometry data. The optimum gas flow ratio for efficient light emission was found to be 1.58. The multilayers consist of 20 alternating layers of a-SiNx:H material as the well and SiO2 as the barrier layers. The growth condition for a-SiNx:H well layer was chosen to be the same as the sample with gas flow ratio of 1.58, since it was found to be the optimum condition for PL efficiency. The SiO2 barrier layer were grown using N2O and SiH4 as O and Si source gases. To study the effect of well layer thickness, two different multilayer structures with fixed barrier layers of 10 nm and well layer thicknesses of 3 and 6 nm were fabricated. The complex refractive index of the a-SiNx:H well layers and SiO2 barrier layers were determined from SE data fitted to a model utilizing Tauc-Lorentz and Cauchy dispersions to describe the well and barrier materials respectively. The layer thicknesses obtained from SE results are in good agreement with the ones measured from TEM graphs. To achieve a high efficiency EL, we have used a structure where electric current is injected laterally and parallel to the multilayer structure. In this way, the current mainly flows only through the well layers and not the barrier layers, and hence the injection process is expected to be more efficient. In total, 20 layers of alternate a-SiNx:H well and SiO2 barrier layers with respective thicknesses of 6 nm and 5 nm were grown. N2O and SiH4 were used as the source gases for SiO2 barrier layer deposition. A post annealing process at 1000oC for one hour in N2 ambient was performed to enhance the PL intensity. To make the contacts for lateral injection of current, we have etched away the multilayer using reactive ion etching and deposited heavily doped n and p type poly Si on each side of the multilayer structure forming interdigitated contacts. For comparison, a similar multilayer structure has been grown for the fabrication of devices with electric field applied vertically. Heavily n-doped Si substrate and a 100 nm thick layer of heavily doped p-type poly Si were used as the bottom and top electrodes respectively. The current-voltage relation of the laterally injected PIN structure indicates good rectifying characteristics of the device. A significant improvement of more than nine orders of magnitude has been observed in the laterally injected device as compared to the vertical one. This can be attributed to the absence of highly resistive barrier layers in the current path. We have observed orange color EL from the device under forward bias condition, a result of radiative recombination of electron hole pairs injected from the n and p poly Si.